Symboland conceptin a language pictureof the world:similarities and differences(on the basis of the Kazakhand Chineselanguages) (Journal of Oriental Studies, 2016)
This article discusses conceptually significant symbolic and significantestimatedcharacteristicsof different colorsin the composition ofChineseproverbs, identifiedtheir ethnicrelevance,for comparis onresistant Kazakhfolksayings.
Keywords: symbol; concept; culture; system of symbols